The influence of the conditions of microplasma processing (microarc oxidation in anodecathode regime) of aluminum alloys on their phase composition - Belozerov, Valery; Sоbоl, Oleg; Mahatilova, Anna; Subbotinа, Valeria; Tabaza, Taha A.; Al-Qawabeha, Ubeidulla F.; Al-Qawabah, Safwan Moh`d (Eastern-European Journal of Enterprise Technologies, 2017)
Investigations have been performed on the effect of microplasma oxidation regimes in electrolytes with activating additives on the phasestructural state of coatings formed on the basis of aluminum. In microarc oxidation (MAO), the surface layer of the processed aluminumbased alloy was converted to a coating consisting of aluminum oxides with increased hardness. Such a modification of the surface layers makes it possible to use the properties of base materials and modified layers most rationally, sparing expensive and rare metals and alloys. The study has revealed the formation of intermediate phases (multistage) during the formation of coatings on aluminum alloys in the alkalisilicate electrolyte and the anodecathode mode of microplasma oxidation. The main intermediate phases are γAl2O3 and 3Al2O3·2SiO2. The composition of the electrolyte has a significant effect on the initial stages of the process during which strong passivating layers are formed on the metallic surface. These layers determine the possibility of spark explosions of sufficient intensity and, thus, the implementation of the MAO process. The obtained results indicate that during the oxidation process, the γAl2O3 phase is alloyed with the base components and the electrolyte components to form solid substitutional solutions. The change in the lattice period in this case will be determined, on the one hand, by the difference in the ionic radii of atoms in the lattice and, on the other hand, by the difference in valence. The paper discloses the influence of the crystalchemical characteristics of the cations of the processed alloy and the cations that make up the electrolyte on the γAl2O3→αAl2O3. The absence of the hardest phase of αAl2O3 (corundum) in the coating is explained by the low power of microdischarges, at which the temperature of the polymorphic γ→α transformation is not ensured. Pilotindustrial tests were performed on friction pair parts, and recommendations have been given on the change in the composition of the electrolyte and the parameters of electrolysis that ensure an increase in the content of the αAl2O3 phase in the coating composition.